The Effect Of Grape Seeds Extract On Hypothyroidism Induced Carbon Tetrachloride In White Mices (Journal of Hama University, 2025)
This study aimed to determine the effect of aqueous grape seeds extract on the levels of (FT3, FT4, TSH) in the blood serum of White mice suffered from hypothyroidism induced with carbon tetrachloride, and promoting it’s therapeutic capacity.The study included 30 adult females mice of the Balb/c strain, which were divided into three groups (10 mice in each group), where the first group (physiological control) was treated with oral cavity 0.9%Nacl until the end of the experiment, while the second group (pathologyical) was injected with carbon tetrachloride in a dose 1mg/kg only once and left for10 days, to be introduced for hypothyroidism, the third group is the treatment group was introduced hypothyroidism, then they were treated by oral cavity whith of 200mg/kg agueous extract of grape seeds daily for 30 days.The results of statistical analysis showed the effectiveness of aqueous grape seed extract in treating hypothyroidism resulting from increased oxidative stress with carbon tetrachloride, It caused a significant increase (P
Keywords: grape seed extract, CCL4, hypothyroidism, TSH, FT3, FT4, mice.